THE ROLE OF AGRICULTURAL EXTENSION WORKERS IN SUPERVISING RICE FARMING AFTER HYDROMETEOROLOGICAL DISASTER IN DEWANTARA DISTRICT NORTH ACEH REGENCY - Nopri Yanto; Setia Budi; Eva Wardah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Agricultural extension workers play a strategic role in assisting farmers to restore and improve the productivity of irrigated rice farming following hydrometeorological disasters. This role includes providing motivation, facilitating access to technology and production inputs, disseminating innovations, and strengthening farmers' capacity to cope with disaster risks. This study aims to analyze the role of agricultural extension workers in assisting irrigated rice farming operations following hydrometeorological disasters in North Aceh Regency. The study employed a quantitative descriptive method using a survey approach. Respondents were irrigated rice farmers affected by hydrometeorological disasters who were under the guidance of agricultural extension workers. Primary data were collected through interviews using a questionnaire designed based on indicators of the extension workers' roles, while the data were analyzed descriptively using a Likert scale. The results indicate that the roles of agricultural extension workers as facilitators, motivators, and educators were rated highly in supporting the recovery of irrigated rice farming operations following the disaster. However, the extension workers' roles in expanding farmers' access to production inputs, climate change adaptation technologies, and strengthening farmer institutions still need to be enhanced so that the resilience of rice farming operations against hydrometeorological disasters can be achieved sustainably.